Ethnic stereotypes, metastereotypes, and intergroup attitudes of ethnic minority university students in China: Mediation of intergroup anxiety - Yao, Shujing; Mohd Khir, Azlina; Ma’Rof, Aini Azeqa; Wan Jaafar, Wan Munira (Scientific Journal, 2025)
We examined the mediating role of intergroup anxiety in the relationships of ethnic stereotypes and metastereotypes with intergroup attitudes of 420 students who belonged to ethnic minorities and who were at universities in Hunan Province, China. The students completed measures of ethnic stereotypes, metastereotypes, intergroup anxiety, and intergroup attitudes, including the Multigroup Ethnic Identity Measure and an intergroup anxiety scale. Mediation analysis revealed that intergroup anxiety significantly mediated the relationship between ethnic stereotypes and intergroup attitudes, but not between metastereotypes and intergroup attitudes. However, metastereotypes had a direct negative effect on intergroup attitudes. These findings support integrated threat theory and extend social identity theory by highlighting distinct pathways in intergroup dynamics. Results suggest that interventions targeting stereotypes and anxiety can foster positive intergroup attitudes in diverse educational settings.